Effect of Couple Stresses on Peristaltic Flow in a Doubly Connected Region - Rashmi, K. R.; Ramarao, Indira; Jagadeesha, S.; Sreegowrav, K. R. (Communications in Mathematics and Applications, 2023)
An eccentric annular region created by insertion of endoscope or catheter in a blood vessel is considered. A sinusoidal wave is assumed to propagate on outer wall, inner wall being rigid. A fully developed flow of couple-stress is assumed in the annular region subject to approximation of long wavelength. Analytical solution is obtained for pressure gradient and axial velocity using regular perturbation method. Average flow rate \(\bar{Q}\) is fixed. The effect of azimuthal coordinate \(θ\), couple stress parameter \(α\) and eccentricty \(ε\) are studied.